2004
DOI: 10.1074/jbc.m401751200
|View full text |Cite
|
Sign up to set email alerts
|

Natural Phosphatidylcholine Is Actively Translocated across the Plasma Membrane to the Surface of Mammalian Cells

Abstract: The cell surface of eukaryotic cells is enriched in choline phospholipids, whereas the aminophospholipids are concentrated at the cytosolic side of the plasma membrane by the activity of one or more P-type ATPases. Lipid translocation has been investigated mostly by using short chain lipid analogs because assays for endogenous lipids are inherently complicated. In the present paper, we optimized two independent assays for the translocation of natural phosphatidylcholine (PC) to the cell surface based on the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…However, facts are modest at best, as most studies addressing membrane lipid asymmetry employed short-chain fluorescent lipids as transport or ''flippase'' substrates, which may be recognized as ''drugs'' rather than natural membrane lipids. Hence, reconstituted in vitro systems [92], as well as natural lipid substrates [89], will be necessary to unequivocally demonstrate functions for ABC transporters in phospholipid homeostasis. During the past years, intensive research efforts led to a better understanding of the molecular mechanisms of members of the ABC protein family.…”
Section: Discussionmentioning
confidence: 99%
“…However, facts are modest at best, as most studies addressing membrane lipid asymmetry employed short-chain fluorescent lipids as transport or ''flippase'' substrates, which may be recognized as ''drugs'' rather than natural membrane lipids. Hence, reconstituted in vitro systems [92], as well as natural lipid substrates [89], will be necessary to unequivocally demonstrate functions for ABC transporters in phospholipid homeostasis. During the past years, intensive research efforts led to a better understanding of the molecular mechanisms of members of the ABC protein family.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot preclude that endogenous PC is transported by ABCA1. Recently, it has been suggested that ABCB1 and ABCB4 are involved in cell surface translocation of natural PC (31). However, these transporters have been shown to recognize NBD analogues of PC as well.…”
Section: Involvement Of Abca1 In Transport Ofmentioning
confidence: 99%
“…ABCB4 (MDR3) and its mouse homologue (mdr2 Pgp) transport PC (31,(33)(34)(35)(36)(37). In contrast, ABCB1 (MDR1 Pgp), giving rise to a frequent form of pleiotropic resistance in tumor cells, transports various lipid analogues (18,23,36,38) and probably also the endogenous lipids platelet-activating factor (a short-chain PC), phosphatidylcholine, phosphatidylserine, and glucosylceramide (18,31,39,40) from the cytoplasmic to the exoplasmic plasma membrane leaflet. ABCC1 (MRP1), belonging to the ABCC family, was reported to mediate outward transport of C6-NBD-PC and -PS in murine erythrocytes (41,42) and NBD-sphingolipids in epithelial cells (43).…”
Section: Involvement Of Abca1 In Transport Ofmentioning
confidence: 99%
“…In turn, lipid transfer could be altered through the presence or conformational change of peptides (24) or translocase proteins (25,26), as has been observed for alamethicin and PS lipids (27). In Fig.…”
Section: Differences Between Planar Bilayers and Supported Bilayersmentioning
confidence: 99%